Pelaksanaan Sistem Administrasi Pelayanan Publik Secara Online Terhadap Permohonan Hak Atas Tanah - Juprianta J.; Anriz N. Halim; Yuliasara Y. (Jurnal Nuansa Kenotariatan, 2019)
The land law policy covers a fundamental aspect, namely the principle of fulfilling people's constitutional rights in order to fulfill the needs of daily life and respect the principle of human equality. To realize the expectations to be achieved as set out in the orderly chess policy of Land, the Land Office as an official government institution authorized to regulate and issue land certificates, in carrying out its daily duties is not spared public attention regarding the performance of the services they provide for people who use their services. The method used in this research is normative legal research. The legal theory used is the theory of legal certainty and authority theory. Results of the research Legal certainty in the implementation of an online public service administration system against the request for land rights, with the existence of these provisions regulates the validity / legality and at the same time legal certainty that guarantees that electronic documents both general and special such as land certificates or other authentic deeds made by PPAT or Notary, Obstacles to the implementation of an online public service administration system against land rights requests, by implementing the PERMATA Government work program seeking to minimize the amount of obligation that must be paid by only charging the Land Price for NJOP determination.